Biotechnological Applications of Extremophilic Microorganisms - Abouhmad, Adel; Schippers, Axel; Rehamnia, Baraa; Adalsteinsson, Bjorn T.; Funk, Christiane; Verseux, Cyprien; Correa-Llantén, Daniela; Ron, Emanuel Y.C; Capo, Eric; Galinski, Erwin A.; Nordberg Karlsson, Eva; Sarmiento, Felipe; et al. (Life in Extreme Environments ;, 2020)
This book provides a broad overview how extremophiles can be used in biotechnology, including for the production and degradation of compounds. It reviews various recent discoveries and applications related to a large variety of extremophiles, considering both prokaryotes as well as eukaryotes.